Peripheral ostema of the mandible: Clinical Case - Etienne Romanelli Terra; Flávia Maria de Moraes Ramos; Petrus Peraira Gomes; Luis Augusto Passeri; Frab Norberto Bóscolo (Universidade Estadual de Campinas, 2015)
This reports a case of peripheral osteoma occurring at the mandibular border in a 16-year-old girl. Clinically, a swelling with a hard surface was observed at the inferior border of the right mandibular body, causing facial asymmetry. Radiographic examination revealed radiopacity and a well-circumscribed mass approximately 2 cm in size. The lesion was treated surgically. The histopathological evaluation revealed features compatible with osteoma, such as vital compact and mature medullary bone tissue, showing osteocytes and medullary spaces containing a loose connective tissue with capillaries. There was no evidence of any recurrence.